Systematic literature review: Implementasi insersi nilai antikorupsi di sekolah dan perguruan tinggi (Komisi Pemberantasan Korupsi, 2023)
Indonesia has a serious corruption problem. All parties must participate in finding solutions to this issue, both through punitive and preventative measures. Education must have a role as a medium for building moral character. This study intends to explore anti-corruption value insertion implementation across a range of academic and extracurricular endeavors. A systematic literature review is applied in this study. This research reviews and analyzes articles on various anti-corruption value insertion strategies. This study makes use of 44 collected articles published within the last seven years. There have been several instances of anti-corruption value insertion through a variety of mechanisms. Anti-corruption principles can be indoctrinated within individuals through a variety of methods such as integration into subjects or courses, the use of teaching techniques, extracurricular activities, and administration or education management with an anti-corruption philosophy. Numerous parties have been active in anti-corruption preventative efforts. Therefore, it is hoped that this endeavor will support the government's plan for eradicating corruption.